Trace element contents in uncultivated surface soils in the Kavala area, northern Greece - Papastergios, G.; Filippidis, A.; Christofides, G.; Kassoli-Fournaraki, A.; Fernândez-Turiel, J. L.; Georgakopoulos, A.; Gimeno, D. (Bulletin of the Geological Society of Greece, 2007)
A total of 65 uncultivated surface soils samples from the area surrounding the city of Kavala, Northern Greece, was collected and analyzed for their abundance in 22 trace elements. The extraction of the elements from the < 200μm soil fraction was based on the digestion of 0.1 g of each sample with 2 ml HNO3. The analytical methods used were ICP-OES and ICP-MS and the elements analyzed were Ag, As, B, Ba, Cd, Co, Cr, Cs, Cu, Hg, Μη, Mo, Ni, Pb, Sb, Se, Sn, Sr, Ti, V, W, and Zn. The chemistry of the surrounding rocks and mineralizations has mainly affected the trace elements contents of the surface soils samples. The average elemental concentrations of the 65 uncultivated surface soil samples were compared with the average values for normal soils of the USA. Arsenic, Pb, andZn were found to be enriched in the surface soils of the present study by a factor of 7.6, 3.3, and 2.7, respectively, indicating that human activities have contributed to their enrichment, since these elements are strongly connected to the industrial and agricultural activities in the area.